REFRACTORY SARCOIDOSIS - Mahmood, Khalid; Butt, Nauman Ismat; Ashfaq, Fahmina; Younus, Raheel (Journal of Ayub Medical College Abbottabad, 2023)
A multi-organ granulomatous disease with characteristic lung manifestations, sarcoidosis generally responds well to glucocorticoid therapy but 10% of cases are refractory necessitating immunosuppressive therapy. A 58-year-old lady presented with dry cough and progressively worsening shortness of breath for last 12 months. On investigation, her ESR was raised but cultures, malignancy screen and TB quantiferon were negative. HRCT chest demonstrated multiple pulmonary nodules with hilar lymphadenopathy and CT guided biopsy revealed non-caseating granuloma. She was diagnosed with Pulmonary Sarcoidosis and started on oral steroids with minimal improvement. Azathioprine was added but due to gastric intolerance switched to methotrexate. Her disease however continued to worsen and infliximab was started but she developed severe allergic reaction. She was then started on mycophenolate mofetil but her chest imaging continued to worsen. After failing prednisone, azathioprine, methotrexate, infliximab and mycophenolate mofetil, the patient was started on rituximab.